2014
DOI: 10.1007/s11136-014-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Girls’ quality of life prior to detention in relation to psychiatric disorders, trauma exposure and socioeconomic status

Abstract: The particularity of each domain of QoL supports a multidimensional conceptualization of QoL. Regarding treatment, psychological health appears as a domain of major concern, while social relationships might serve as a source of resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Also, each domain of QoL was affected by specific mental health problems. In support of the GLM's first assumption, psychiatric disorders were negatively related to detained girls' QoL (Van Damme et al, 2015). The cross-sectional nature of this latter study (Van Damme et al, 2015) did not allow to determine whether a low QoL increased the odds of future mental health problems and offending (second GLM assumption).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Also, each domain of QoL was affected by specific mental health problems. In support of the GLM's first assumption, psychiatric disorders were negatively related to detained girls' QoL (Van Damme et al, 2015). The cross-sectional nature of this latter study (Van Damme et al, 2015) did not allow to determine whether a low QoL increased the odds of future mental health problems and offending (second GLM assumption).…”
mentioning
confidence: 93%
“…In support of the GLM's first assumption, psychiatric disorders were negatively related to detained girls' QoL (Van Damme et al, 2015). The cross-sectional nature of this latter study (Van Damme et al, 2015) did not allow to determine whether a low QoL increased the odds of future mental health problems and offending (second GLM assumption). The few empirical studies in adult offenders testing this second GLM assumption indicated that a low QoL does put them at risk for recidivism (Bouman, Schene, & de Ruiter, 2009;Willis & Grace, 2008; and supported the existence of the abovementioned direct and indirect pathways toward offending (Purvis, 2010).…”
mentioning
confidence: 93%
“…Less is known about QoL in detained juveniles. The few studies that were performed focused on youth in secure residential care, juvenile offenders’ health-related QoL, or QoL of detained girls exclusively [ 6 , 24 – 26 ]. Girls with low QoL prior to detention were at an increased risk for mental health problems post release, increasing the risk of offending [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians and researchers emphasize the need to organize effective treatment services for these girls (Teplin, Abram, McClelland, Dulcan, & Mericle, 2002;Wasserman, McReynolds, Ko, Katz, & Carpenter, 2005). However, detained girls may not be willing to engage in treatment due to the coercive nature of juvenile justice settings (van der Helm, Beunk, Stams, & van der Laan, 2014), because their psychiatric state may hinder treatment engagement (van Binsbergen, Knorth, Klomp, & Meulman, 2001), or because they seem relatively satisfied with their quality of life (Van Damme, Colins, De Maeyer, Vermeiren, & Vanderplasschen, 2015). Clearly, engaging detained girls in treatment poses great challenges.…”
Section: Introductionmentioning
confidence: 99%